The Influence of Tax Understanding, Taxpayer Awareness, and Government Trust as a Moderating Variable on Taxpayer Compliance (Empirical Study on MSMEs Registered at the Jakarta Palmerah Pratama Tax Office) - Endrianto, Fauzy; Nugroho, Lucky (Pelita : Jurnal Penelitian, Terapan dan Aplikatif, 2025)
This study aims to examine the extent to which tax understanding, taxpayer awareness, and trust in the government affect the tax compliance of Micro, Small, and Medium Enterprises (MSMEs). The phenomenon at KPP Pratama Jakarta Palmerah indicates a discrepancy between the increase in the number of registered MSMEs which increased from 6,005 in 2020 to 7,241 in 2024, and the decrease in the number of tax reports from 1,588 to 1,469. This condition indicates that the level of MSME tax compliance remains relatively low. This study employs a quantitative approach using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. A total of 100 MSME actors were selected through an accidental sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, R² value, goodness of fit, and hypothesis testing through bootstrapping. The results show that tax understanding, taxpayer awareness, and trust in the government have a positive and significant effect on tax compliance. However, trust in the government has not been shown to strengthen the relationship between understanding or awareness and compliance. These findings confirm that internal taxpayer factors play a dominant role in shaping compliance, while trust in the government serves as an independent supporting factor.